2021
DOI: 10.1186/s12872-020-01846-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of lipid parameters to identify apparently healthy men at high risk of arterial stiffness progression

Abstract: Background Dyslipidemia contributes to the development and progression of arterial stiffness. We aimed to identify the most informative measures of serum lipids and their calculated ratios in terms of arterial stiffness progression risk. Methods Total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and brachial-ankle pulse wave velocity (baPWV) of 659 healthy males (47.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
(55 reference statements)
3
9
0
2
Order By: Relevance
“…Our study shows that TG/HDL was more often associated than other lipid parameters (such as isolated lipids and other lipid ratios) with ASI in a middle-aged population free of CV disease. This result was consistent with other studies in young, healthy populations ( 22 , 46 ). Lp(a) was not associated with AS in our study, in concordance with other recent studies ( 49 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study shows that TG/HDL was more often associated than other lipid parameters (such as isolated lipids and other lipid ratios) with ASI in a middle-aged population free of CV disease. This result was consistent with other studies in young, healthy populations ( 22 , 46 ). Lp(a) was not associated with AS in our study, in concordance with other recent studies ( 49 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, in comparison with the isolated LDL parameter, these parameters remained nonsignificant unlike TG/HDL. As observed in previous studies, these parameters showed a significant relationship with AS ( 21 , 46 , 59 ). However, the findings observed could be the result of a decrease in the antiatherogenic constituent of the denominator (i.e., HDL) ( 60 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The lack of association between the Meat DP with the cardiovascular phenotypes, considering the cumulative risk factors described previously, may be related to the protective effect of younger age, as this study included a broad age range with most participants at middle age. Although we did not find clinical manifestations of cardiovascular disease, it should be taken into consideration that these participants had higher TG and TG/HDLc ratio and these markers have recently shown to predict arterial stiffness progression [ 56 ]. Thus, they may be at an increased risk of arterial stiffness although the cumulative damage on the vascular wall are not evident yet.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis performed by Sang et al, TG values, as well as TG/HDL-C index, were documented to be associated with increased PWV and can indicate the high risk of progression of AS in healthy men [ 71 ].…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%